Wskaźnik palców a budowa ciała i sprawność motoryczna mężczyzn trenujących sporty walki i nietrenujących = The digit ratio 2D:4D and body build and motoric fitness of men training martial arts and non-athletes - Magdalena Mońka; Jadwiga Pietraszewska (Kazimierz Wielki University, 2016)
Mońka Magdalena, Pietraszewska Jadwiga. Wskaźnik palców a budowa ciała i sprawność motoryczna mężczyzn trenujących sporty walki i nietrenujących = The digit ratio 2D:4D and body build and motoric fitness of men training martial arts and non-athletes. Journal of Education, Health and Sport. 2016;6(12):412-423. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.204647 http://ojs.ukw.edu.pl/index.php/johs/article/view/4071         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 15.12.2016.       Wskaźnik palców a budowa ciała i sprawność motoryczna mężczyzn trenujących sporty walki i nietrenujących   The digit ratio 2D:4D and body build and motoric fitness of men training martial arts and non-athletes   Magdalena Mońka1, Jadwiga Pietraszewska2   1 Doktorantka na Wydziale Wychowania Fizycznego Akademii Wychowania Fizycznego we Wrocławiu 2 Zakład Antropologii Fizycznej Akademii Wychowania Fizycznego we Wrocławiu   Słowa kluczowe: wskaźnik 2D:4D, sporty walki, budowa ciała, sprawność motoryczna Key words: index 2D:4D, martial arts, body build, motoric fitness     mgr Magdalena Mońka, dr hab. Jadwiga Pietraszewska, prof. nadzw.     Streszczenie               Poziom sprawności fizycznej jest uwarunkowany wieloma czynnikami, w tym również budową morfologiczną. Jednym z elementów morfologicznych jest formuła palców 2D:4D, opisująca stosunek długości palca drugiego do palca czwartego. Wskaźnik palców kształtuje się w życiu płodowym, pod wpływem działania hormonów płciowych i pozostaje niezmiennym w dalszym rozwoju osobniczym. Wysoki poziom testosteronu, odzwierciedlający się w niższych wartościach formuły palców, determinuje lepszą zręczność, wytrzymałość i siłę. Ponadto wpływa na zachowania zawodników, zwiększając skłonność do agresji oraz wolę walki i podjęcia ryzyka.   Cel               Celem niniejszej pracy jest ocena powiązań wskaźnika palców 2D:4D z cechami budowy somatycznej oraz poziomem sprawności motorycznej w grupie zawodników sporów walki i osób nietrenujących. Materiał i metody               Materiał badawczy stanowiły pomiary antropometryczne i wyniki prób motorycznych mężczyzn uprawiających sporty walki (n=28) oraz osób nietrenujących (n=30). Badani to studenci Akademii Wychowania Fizycznego we Wrocławiu w przedziale wiekowym 19-25 lat. U wszystkich badanych zmierzono cechy długościowe, szerokościowe, obwody ciała i fałdy skórno-tłuszczowe oraz długość drugiego (2D) i czwartego palca (4D) prawej i lewej ręki. Do oceny sprawności motorycznej badanych wykorzystano cztery próby motoryczne: skłon w przód w siadzie, skok w dal z miejsca, siady z leżenia, pomiar dynamometryczny ręki prawej i lewej. Próby zostały przeprowadzone zgodnie z procedurą testu Eurofit.   Wyniki               Analiza wyników wykazała istotne różnice wskaźnika palców między badanymi grupami. Stwierdzono też powiązania tego wskaźnika z cechami budowy somatycznej u badanych mężczyzn. Nie odnotowano natomiast istotnych zależności formuły palców z wynikami prób motorycznych.       Summary               The level of physical fitness is conditioned by many factors, including build morphological. One of the morphological elements is digit ratio 2D: 4D. Index finger forms in fetal life under the influence of sex hormones and it remains constant in the further ontogenetic development. High testosterone level, reflecting the lower value digit ratio, determines a better agility, endurance and strength. In addition, it affects the behavior of players, increasing the tendency to aggression and will to fight and take risks.      Aim                                The aim of the study is estimation relationship of digit ratio 2D: 4D with the somatic features and the level of motor skills in a group of men training martial arts and non-athletes. Material and methods               The researches are conducted in group of 28 men training martial arts and group of 30 non-athletes men. All of them were students of University of Physical Education. The age of examined was 19-25. There was measured digit ratio, basic anthropological features and motoric fitness. There was used four motoric tests: sit-ups, standing long jump, flexibility and hand grip strength. Conclusion               The analysis of the results has showed significant differences of digit ratio between the examined groups. There is the correlation of this indicator with the somatic features in both groups. However there were any significant correlations of digit ratio with the results of motoric tests.